(untitled) (Journal of Parents and Teachers, 2014)
This article talks about secular, illustrated, civic, spiritual and religious tolerance and takes as a role model a poem by Federico García Lorca named “The encounters of an adventurous snail”. Federico García Lorca, as a symbol for culture, peace and love, gave cordiality and educative arts diffusion.